Perancangan Aplikasi Konversi RGB CMYK berbasis Python - Pratama, Yoga Putra; Prastiwinarti, Wiwi; Ahmad, Luthfiandra; Mahmuda, Zain Sultan (Journal of Applied Electrical Engineering, 2023)
Color is one important component in the printing process. Colors on digital displays have different formats when it comes to printing. This research aims to design an alternative in using an application, and the approach employed in this study makes advantage of the Adobe RGB color standard for testing. The programming language used is Python, which has supporting libraries for designing such applications. The results of the research are images consisting of each color component, C, M, Y, K. This study's conclusion is that the Python programming language can support the creation of this color conversion application and it is easy to design due to sufficient support in application development.